Optimizing Social Media Usage for Community Education and Islamic Financial Literacy Development at Islamic Banking Schools - Syamsiah Muhsin; Hasmawati Hasmawati; Dian Novianti; Nursyamsiah Nursyamsiah; Nur Annida Ahmad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study examines the effect of optimizing social media usage on community education and its impact on enhancing Islamic financial literacy among students at Islamic Banking Schools. Social media optimization is considered a strategic tool for disseminating financial knowledge and promoting Islamic values that align with the needs of younger generations. The research employed a quantitative approach using Structural Equation Modeling (SEM). Data were collected through surveys administered to 93 purposively sampled students from Islamic Higher Education Institutions in South Sulawesi. The results reveal that social media optimization has a significant positive effect on community education. Furthermore, community education is important in improving students’ Islamic financial literacy. Another key finding indicates that community education partially mediates the relationship between social media optimization and Islamic financial literacy. In conclusion, the study highlights the importance of integrating well-managed social media platforms with structured educational programs to strengthen Islamic financial literacy in academic environments. Practical recommendations suggest that Islamic Banking Schools should invest in developing interactive and culturally relevant digital content, while also enhancing the capacity of educators and media managers to maximize engagement and ensure effective knowledge dissemination.